Investigation of glutamic acid production capacity of Stenotrophomonas sp. strain CG2 isolated from soil - Guner, Cihat; Ermis, Ertan; Guner, Kubra Ozkan (ELSEVIER, 2025)
Glutamic acid is a widely used amino acid in the food and pharmaceutical industries due to its role as a flavor enhancer and a metabolic precursor. This study aimed to identify glutamic acidproducing bacterial strains from soil samples collected across different regions. Among 262 isolates screened, Stenotrophomonas sp. strain CG2 exhibited the highest production capacity and was identified through 16S rRNA sequencing. Fermentation parameters including pH, temperature, incubation time, and agitation speed were optimized using the Plackett-Burman design, leading to a maximum yield of 3.76 +/- 0.65 g/L under optimized conditions (pH 7.0, 30 degrees C, 200 rpm, 84 h), compared to 2.72 g/L in unoptimized TSB medium. The produced glutamic acid was purified using ion-exchange resin, yielding a recovery efficiency of 53.48 +/- 3.28 %, and its identity was confirmed by FT-IR, RAMAN, and LC-MS/MS analysis. This study is among the first to systematically explore Stenotrophomonas spp. for glutamic acid biosynthesis under optimized fermentation conditions. The results provide insight into the strain's specific responses to nutrient composition, revealing its potential for future biotechnological applications. By expanding the microbial landscape of amino acid producers, this work offers a foundation for using CG2 in sustainable bioproduction processes, particularly those leveraging food or agro-industrial waste streams.
Keywords: Glutamic acid; Microbial fermentation; Stenotrophomonas sp; Food additives; Amino acids; Fermentation optimization; MONOSODIUM GLUTAMATE; RAMAN; FERMENTATION; OPTIMIZATION; Biotechnology & Applied Microbiology